Dynamisme du néo-gothique, architecture du renouveau religieux : le débat sur la création architecturale dans les années 1840 : A. W. N. Pugin et J. H. Newman - Odile Boucher-Rivalain (Revue LISA)
The Oxford Movement and the many religious controversies it raised did not fail to have a strong impact beyond strictly theological issues. The architectural criticism of the early Victorian period bears the marks of the passionate debate around the Catholic revival in England in the 1830s and 1840s. This article examines the significant opposition between two radically opposed visions, that of A.W.N. Pugin, the leading figure of the ritualist movement and architectural critic, contrasting with that of J.H. Newman, the well-known theologian and thinker. While the former advocated architectural decoration in the Gothic style as its most perfect form, best suited to the expression of Catholic faith, the latter found the essence of religion not in the visible manifestations of faith but in interior contemplation. The polemical aspect of Pugin’s opposition to Newman is exemplified by his quarrel with The Rambler, a Catholic journal supported by Newman, concerning an article on town churches, published in January 1850.